Jointing design in open plan office system - Dolah, Mohd Shahrizal; Mohd Yusuff, Rosnah; Abdul Rahman, Ahmad Rizal; Osman, Mohd Rasid (2005)
Most modern offices use open plan office system due to the flexibility of the product. The open plan office system (OPS) can be customized from low screen to high screen and can be installed and dismantled according to the office needs. According to MIDA (Malaysian Industrial Development Authority) the total sales for Malaysian office furniture industries was RM 1.6 billion in 2003 of which 7.2% (115. million) comes from sales generated from the open plan office system. The sales report showed the importance of the open plan office system in creating the office environment. Since the demand of OPS is increasing, effective ways of assembling the system is required. Most OPS uses bolts and nuts to join the panels. However, this jointing system requires many parts and the assembly process is time consuming. A survey carried out in this study on manufacturers of OPS identified the main criteria for the jointing system design is to increase the efficiency during the assembly process. One of the important functions of the jointing systems is to ensure that the system can be provided with flexibility during the assembly process. Based on these findings, the study looked into various jointing system that can satisfy all these requirements. The paper reports on two proposed design of the jointing system that may fulfill these requirements. Simulation studies were carried out on the proposed design and the strength of the joints. The research is limited to the tiles system. Both designs concept were based on the snap fit concept and both were found to be better than the current design not only in terms of ease of assembly but also efficiency.